Algorithmic Models for MicroBlog Information Mining System. (June 2020) - Leng, Jing; Xu, Wei
Abstract: Based on the "MicroBlog Community Massive Information Mining and Monitoring System", this paper introduced the algorithm and model construction of microblog information word processing and mining conversion core functions of microblog information subsystem, in order to obtain the information objects needed in each link of the process of microblog information mining, which provides a basis for the realization of monitoring and early warning in the MicroBlog monitoring platform.